Sugar and amino acid preference in the black garden ant Lasius niger (L.). (July 2017) - Madsen, Natalia E.L.; Sørensen, Peter B.; Offenberg, Joachim
Highlights: L. niger 's preference for different sources of sugar and amino acids was measured. Solutions based on sucrose were significantly preferred over monosaccharides. Trisaccharides increased the attractiveness of sucrose solutions. Varied solutions of peptides and amino acids were preferred over less varied ones. Food preference in L. niger is context dependent. Abstract: The mutualistic relationship that the garden ant Lasius niger (L.) establishes with trophobiotic homopterans makes this ant an unwelcome host in commercial crops, as ants improve the survival of homopteran pests from which they collect honeydew as a source of carbohydrates. Because the offering of alternative sugar sources can be used to disrupt this relationship, the present study explored L. niger 's preference towards sugar and amino acid components that may be used in sugar solutions to increase their attractiveness. We tested the ant's preference between basic sugars (mono- and disaccharides) used as main ingredients and attractants (trisaccharides and amino acid (AA) sources) added to basic sugar in small amounts. Results showed that ants preferred disaccharides over monosaccharides, and that trisaccharides increased the attractiveness of sucrose solutions, albeit not when a protein source was added to the mix. In the case of AA sources, ants preferred components with a more diverse composition. In conclusion, trisaccharides and AA sources can be used to increase the attractiveness of sugar solutions, leading to the development of solutions that when supplied in artificial feeders can out-compete honeydew and disrupt harmful ant-homopteran mutualisms in agriculture.